HIV-associated sensory neuropathy in the era of tenofovir-based highly active antiretroviral therapy (HAART) - Pillay, Prinisha (My University, 2018)
HIV-associated sensory neuropathy (HIV-SN) is a common and often painful neurological condition associated with HIV-infection and its treatment with neurotoxic antiretroviral drugs such as stavudine. antiretroviral drugs. The prevalence of HIV infection remains high in subSaharan Africa and is expected to stay high in the anticipated future. This high prevalence will persist, irrespective of the reduction in infection rates, due to the improved supply and accessibility of ARV therapies, which significantly improve survival rates. Longer survival rates for people living with HIV/AIDS (PLWHA) will lead to an accumulation of chronic complications associated with HIV infection and its treatment in the population. Furthermore, with the removal of the neurotoxic antiretroviral drug stavudine in all first-line therapies in South Africa and it’s replacement with the supposedly less neurotoxic drug tenofovir, it is anticipated that the incidence of conditions such as HIV-SN will decrease. In my thesis I have focused on HIVSN, a chronic comorbid and often painful condition that can significantly affect quality of life. In the first aspect of my thesis, I investigated the six-month incidence of HIV-SN in ARV naïve individuals initiating updated cART, which consists of the single fixed dose combination (FDC) pill that contains the ARV tenofovir. This single fixed dose conimantion pill contained tenofovir and efavirenz either given with lamivudine (3TC) or emtricitabine (FTC) and is the standard first-line therapy given to all pateints inititating ARV therapy for the first time in South Africa. I also investigated what clinical factors may be associated with the development of HIV-SN in this population. This is important as there is a need to re-examine risk factors for the development of HIV-SN in the setting where stavudine is no longer prescribed. This thesis presents the first longitudinal study to assess the incidence of HIV-SN in a cohort of individuals of 100% black African ancestry, that were universally exposed to TDF-based cART, and the clinical factors associated with the development of HIV-SN. I recruited 120 ARV naïve individuals initiating TDF-based cART at the Lenasia South Local Community Hospital, Johannesburg and assessed HIV-SN using the AIDS Clincal Trials Group (ACTG) Brief Peripheral Neuropathy Screen. Painful HIV-SN was defined as present if the participant had at least one symptom (pain) and at least two signs (reduced vibration sense in the great toe, absent ankle reflexes or decreased pin-prick sensitivity in the feet). Nonpainful HIV-SN was defined as present if the participant had at least two signs (as described above). A total of 83 individuals completed the study, and the cumulative incidence of neuropathy at the end of six-months was 200 cases per 1000 patients (95% CI: 120-290). The incidence rate was 0.47 (95% CI: 0.3-0.67) per person year. Eleven (13%) individuals developed non-painful HIV-SN and nine (11%) developed painful HIV-SN. Asymptomatic SN had a slower onset (>3 months) compared to symptomatic SN, which developed rapidly (within the first 3-month period). The presence of pain was a significant risk factor for the development of HIV-SN (p< 0.001). Increasing height and receiving treatment for a current tuberculosis (TB) infection were independently associated with the risk of HIV-SN. However, other established risk factors for HIV-SN such as increasing age, current CD4 T-cell count and sex were not associated with the development of HIV-SN in our cohort. Our finding of a six-month cumulative incidence of 200 cases per 1000 patients on TDF-based cART who had never previously been exposed to any form of cART indicates that HIV-SN is certainly not a thing of the past, and that the number of new cases is still high. Our finding also contradicts the belief that updated cART therapies, which do not include drugs associated with neurotoxicity, will eliminate new cases of HIV-SN. Participants also donated blood samples across the six-month study period (0, 2, 4, and 6 months) for the extraction of plasma. We used a total of n=119 plasma samples (approximately 30 samples at each time-point), to investigate the possible role of chemokines in the development of HIV-SN. Based on reports in the literature, we selected four chemokines, CCL5 (RANTES), CCL2 (MCP-1), CX3CL1 (Fractalkine) and CXCL12 (SDF-1). We measured the levels of these chemokines at the four time-points using Luminex pre-mixed magnetic bead assays, to assess whether they associated with the development of HIV-SN. Based on the observed concentration values from the assay for the chemokine (CCL5) RANTES, we opted to exclude CCL5 from the chemokine analysis as most values were far outside of the upper limit of the standard curve, indicating that the analyte had not be diluted enough for the assay. We did not find any significant associations between levels of chemokines measured and the development of HIV-SN across the six-month period. The lack of association observed between the levels of chemokines measured and the development of neuropathy, may well be due to the wide and often irregular sampling intervals we faced during collection of patient blood samples. In the third aspect of my thesis, I explored the role of psychological factors including depression, anxiety and catastrophizing in individuals who developed a painful or non-painful HIV-SN. I investigated whether these psychological factors associated with having a painful HIV-SN and whether pain and psychological factors affected quality of life in this South African population. As a secondary objective, I also completed a sub-group analysis of the painful HIV-SN group to determine whether psychological factors predicted the intensity of their neuropathic pain. This study is the first, globally, to assess the relationship between these psychological factors and painful and non-painful HIV-SN. I recruited 197 participants from the Greenhouse Pharmacy, at the Chris-Hani Baragwanath Hospital, Soweto. All participants had a confirmed HIV infection and were currently on ARV therapy. We assessed HIV-SN using the AIDS Clinical Trials Group (ACTG) Brief Peripheral Neuropathy Screen. Painful HIV-SN was defined as present if the participant had at least one symptom (pain) and two signs (reduced vibration sense in the great toe, absent ankle reflexes or decreased pin-prick sensitivity in the feet). Non-painful HIV-SN was defined as present if the participant had at least two signs. One hundred and twenty-five (125/197) participants had painful HIV-SN and seventy-two (72/197) participants had non-painful HIV-SN. Among participants with painful HIV-SN, 85% (106/125) reported their pain as “moderate” to “severe” in intensity, with a median pain intensity of 7 (IQR 1-10). We found that depression, anxiety and pain catastrophizing did not associate with the presence of painful HIV-SN in our cohort. We did find, however, that increased depressive symptoms and the presence (but not intensity) of pain independently associated with reduced quality of life. Furthermore, greater depressive symptoms independently associated with increased pain intensity in patients with painful HIV-SN. Painful HIV-SN is difficult to treat pharmacologically so focusing on improving quality of life and function could be another angle to take therapeutically. Furthermore, placing a greater emphasis on assessing and treating depressive symptoms in patients with SN could be advantageous and may result in a reduction in pain intensities reported. My study is the first in sub-Saharan Africa to report on the present incidence of HIV-SN in the era of TDF-based cART and factors associated with the development of SN in this African population on this regimen. My findings highlight the substantial burden of symptomatic HIVSN, and their detrimental impact on quality of life. My findings further emphasize the need for assessing and treating the high burden of depressive symptoms observed in our population.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg August 2018